9(z-9)-(-7z-1)=15z

Simple and best practice solution for 9(z-9)-(-7z-1)=15z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(z-9)-(-7z-1)=15z equation:


Simplifying
9(z + -9) + -1(-7z + -1) = 15z

Reorder the terms:
9(-9 + z) + -1(-7z + -1) = 15z
(-9 * 9 + z * 9) + -1(-7z + -1) = 15z
(-81 + 9z) + -1(-7z + -1) = 15z

Reorder the terms:
-81 + 9z + -1(-1 + -7z) = 15z
-81 + 9z + (-1 * -1 + -7z * -1) = 15z
-81 + 9z + (1 + 7z) = 15z

Reorder the terms:
-81 + 1 + 9z + 7z = 15z

Combine like terms: -81 + 1 = -80
-80 + 9z + 7z = 15z

Combine like terms: 9z + 7z = 16z
-80 + 16z = 15z

Solving
-80 + 16z = 15z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-15z' to each side of the equation.
-80 + 16z + -15z = 15z + -15z

Combine like terms: 16z + -15z = 1z
-80 + 1z = 15z + -15z

Combine like terms: 15z + -15z = 0
-80 + 1z = 0

Add '80' to each side of the equation.
-80 + 80 + 1z = 0 + 80

Combine like terms: -80 + 80 = 0
0 + 1z = 0 + 80
1z = 0 + 80

Combine like terms: 0 + 80 = 80
1z = 80

Divide each side by '1'.
z = 80

Simplifying
z = 80

See similar equations:

| -5X-15=-7X-3 | | 7x-(1-x)= | | 5s+2s=14 | | 9x-9/5*35/3x-3 | | 5x-x=x+16-x | | 9x-9/5/3x-3/35 | | 3x^2+2-50=0 | | 3.1q-2.9-4.1q=-2.0q-3.9 | | -10.2x=30.6 | | 4(3n+2)-2n= | | 4/5/5 | | 8/7-12/35 | | 2x+x-2/3=144 | | 27x+15y=99 | | 4(w+7)=3w-4 | | (4w+7)=3w-4 | | -n+1+5n+3= | | n/10+4=11 | | 2x^2+32x-160=0 | | 2.5=c/24 | | 4x^3+48x^2+108x=0 | | 0/2/5=0 | | -4v-46=-9(v+4) | | 2/3n-6 | | x+10+20+x=180 | | -7.6(1)=-7.6 | | 2x-1/4=3y | | 11*2.2= | | 0.05*0.22= | | x/2+7=-4 | | 11/4+23/4 | | x=7*(8-y) |

Equations solver categories